2016
DOI: 10.1038/srep36774
|View full text |Cite
|
Sign up to set email alerts
|

Β-blockers treatment of cardiac surgery patients enhances isolation and improves phenotype of cardiosphere-derived cells

Abstract: Β-blockers (BB) are a primary treatment for chronic heart disease (CHD), resulting in prognostic and symptomatic benefits. Cardiac cell therapy represents a promising regenerative treatment and, for autologous cell therapy, the patients clinical history may correlate with the biology of resident progenitors and the quality of the final cell product. This study aimed at uncovering correlations between clinical records of biopsy-donor CHD patients undergoing cardiac surgery and the corresponding yield and phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 64 publications
2
40
0
1
Order By: Relevance
“…This resulted in impairment of nitric oxide availability and APC dysfunction ( 118 ), which ultimately might lead to lower reparative and regenerative capabilities. Consistently, increased miR-21 expression levels have been also associated to features of reduced cardiovascular regenerative potential in human CPCs ( 112 ). Overall these studies suggest that, together with circulating proteins, epigenetic mediators may play a key role in physiologic aging mechanisms in the cardiovascular system, affecting local regenerative potential.…”
Section: Circulating Mirnasmentioning
confidence: 84%
See 1 more Smart Citation
“…This resulted in impairment of nitric oxide availability and APC dysfunction ( 118 ), which ultimately might lead to lower reparative and regenerative capabilities. Consistently, increased miR-21 expression levels have been also associated to features of reduced cardiovascular regenerative potential in human CPCs ( 112 ). Overall these studies suggest that, together with circulating proteins, epigenetic mediators may play a key role in physiologic aging mechanisms in the cardiovascular system, affecting local regenerative potential.…”
Section: Circulating Mirnasmentioning
confidence: 84%
“…Concerning its effects on cardiovascular and regenerative cells, a direct effect of miR-146a on vascular cells’ survival has been described in animal models, where miR-146a overexpression induced vascular smooth muscle cells apoptosis through activation of the NF-KB signaling pathway ( 111 ) (Figure 2 ). Interestingly, features of increased functional cell yield and cardiogenic potential in CPCs have been associated to reduced levels of miR-146a ( 112 ). Moreover, miR-146a overexpression has been shown to increase cell senescence in an EPC-enriched bone marrow cell population, impairing their angiogenic properties ( 113 ).…”
Section: Circulating Mirnasmentioning
confidence: 99%
“…It has been reported that BBs can enhance mesenchymal stem cell therapy for myocardial infarction by increasing cell survival . Moreover, they have been shown to sustain CPC viability and their cardiogenic phenotype in human resident CPCs, while reducing their pro‐fibrotic features, such as collagen I , miR‐21 , and miR‐29 expression levels . Interestingly, BBs have been also associated to successful cardiac recovery, or “reverse remodeling,” during left ventricular assist device (LVAD) support, that is near‐normalization of the multiple myocardial abnormalities in advanced heart failure patients after mechanical unloading through LVAD implantation .…”
Section: Regeneration Against Fibrosismentioning
confidence: 99%
“…In fact, a significantly faster and higher CS-forming capacity was detectable in BB explants compared to NBB. Moreover, an immunophenotypical shift of the described CDC marker CD90 was detectable between the two groups, with a significantly increased percentage of CD90 + cells in NBB [ 122 ]. In the CADUCEUS clinical trial, CD90 expression in injected CDCs negatively correlated with infarct scar size reduction.…”
Section: Rejuvenation Biotechnology: Antisenescence Regenerative Tmentioning
confidence: 99%